Dialysate temperature reduction for intradialytic hypotension for people with chronic kidney disease requiring haemodialysis - Tsujimoto, Yasushi (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: This review aims to evaluate the benefits and harms of dialysate temperature reduction for IDH among patients with CKD requiring HD, compared with standard dialysate temperature. In addition, we will compare the benefits and harms of different types of dialysate temperature reduction for IDH.